Synthesis and C-alkylation of hindered aldehyde enamines. - Hodgson, D; Bray, C; Kindon, N; Reynolds, N; Coote, S; Um, J; Houk, K (2009)
A new reactivity mode of hindered lithium amides with terminal epoxides is described whereby aldehyde enamines are produced via a previously unrecognized reaction pathway. Some of these aldehyde enamines display unprecedented C-alkylation reactivity toward unactivated primary and secondary alkyl halides. For comparison, the reactivity of aldehyde enamines synthesized via a traditional condensation method was examined. C- rather than N-alkylation was the dominant reaction pathway found with a range of electrophiles, making this route to alpha-alkylated aldehydes more synthetically useful than previously reported.